IMPACT OF FIBROMYALGIA ON DAS-28 SCORE IN RHEUMATOID ARTHRITIS: Fibromyalgia in Rhenumatiod Arthrits - Rehman, Ata Ur; Haque, afazzul-E-; Rasheed, Aflak; Wagan, Abrar Ahmed; Asghar, Ammad; Rukh, Syed Ali (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the frequency of fibromyalgia American college of rheumatology (ACR) 2010/2011criteria) in patients with rheumatoid arthritis and its impact on disease activity score (DAS-28).Study Design: Cross-sectional study.Place and Duration of study: Department of Rheumatology and Immunology, Sheikh Zayed Hospital Lahorefrom Jun 2016 to Feb 2017.Patients and Methods: Total 140 diagnosed patients of rheumatoid arthritis by criteria ACR 2010 were includedin this study. ACR modified 2010/2011 criterion of fibromyalgia was used to diagnose co existing fibromyalgia inthese patients. Clinically disease activity status was assessed by standardized and validated DAS-28 calculator;2ml of blood was drawn and sent to laboratory for estimation of erythrocyte sedimentation rate for all studyparticipants.Results: The mean age, duration of disease, DAS-28 of sampled population was 49.12 ± 8.5 years, 7.36 ± 3.8 years,4.08 ± 1.1 respectively. Out of 140 patients, 127 patients (90.7%) were females. Fibromyalgia was diagnosed in41 patients (29.1%). The mean DAS-28 score in patients of rheumatoid arthritis with fibromyalgia was 5.39 ± .58while for patients of without fibromyalgia it was 3.54 ± 0.69 (p-value